FORMULATION AND CHARACTERIZATION OF LOSARTAN LOADED SELF EMULSIFYING DRUG DELIVERY SYSTEM - JATT, KARNITA SINGH; KHARE, BASANT; JAIN, PRATEEK KUMAR; JAIN, HARSHITA; DUBEY, NAINA (International Journal of Current Pharmaceutical Research, 2022)
Objective: The object of the present work was the advancement and portrayal of losartan stacked self-emulsifying drug conveyance framework for the successful administration of hypolipidemia (RSEDDS) for further developing bioavailability, to upgrade dissolvability, delays home time, give an adequate measure of medication to an objective site and supported the arrival of medication. Methods: Self-Emulsifying Drug Delivery System was ready by the basic emulsification method. Six clumps, for example, F1 to F6 were ready by shifting the convergence of oils, surfactant, co-surfactant, and co-dissolvable and assessed for the different boundaries, for example, Optical microscopy, Assessment of self emulsification, Emulsification time, Droplet size investigation, Zeta Potential Measurement, Transmission Electron Microscopy, Viscosity Determination, Drug content, Percentage conveyance, in vitro disintegration study and solidness study. The SEDDS was upgraded and group F5 was additionally utilized. Results: The medication content of chosen clump F5 was viewed as 97.65±1.37 %; it proposes that the technique for exemplification was powerful. As per in vitro study, around 55.13 % of the medication was delivered after 120 min which showed supported arrival of medication and there were no critical changes seen in the actual appearance, drug content, and in vitro drug release during the stability study. Conclusion: This research presumed that the SEDDS are an expected competitor as a supported delivery drug conveyance, effectively expanding bioavailability and designated conveyance of medication.